Scheduling : theory, algorithms, and systems - Pinedo, Michael L. (Springer, 2012)
This fresh edition of a key work on scheduling assesses the latest developments and covers theoretical models as well as real-world scheduling problems. It includes software that contains slide shows from industry and movies on implementing scheduling systems